Patients’ Opinion on Cost of Drugs and Satisfaction with Services Provided in A State Teaching Hospital Eye Clinic, Southeast, Nigeria - Okoloagu, Nkiruka N.; Ndibuagu, Edmund O.; Eze, Christian (British Journal of Healthcare and Medical Research, 2023)
Patients’ opinion on the cost of drugs is usually an indication of how satisfied they are with the cost of drugs in the health facility; and ultimately could contribute to their continued usage of the facility, or discontinuing usage. The study aimed at assessing patients’ opinion on cost of drugs in a tertiary health facility Eye clinic, and also finding out their overall satisfaction level with services provided at the health facility Eye clinic. The research was a cross-sectional study, using 348 respondents; and the study was conducted for a period of two months in 2022. Most of the respondents were females (63.5%), of Igbo tribe extraction (94.8%), Christians (96.6%), and married (63.2%). About half of the respondents perceived cost of drugs as affordable/very affordable (51.1%), while 75.5% were satisfied/very satisfied with services provided at the Eye clinic. Though both opinion on cost of drugs, and overall satisfaction with services provided at the health facility Eye clinic were good; it is still recommended that the management of the health facility should work towards improving on this. This ultimately will contribute to improved eye health for people who are residing within the catchment area of the tertiary health facility.